Physical Profile of West Java Taekwondo Athletes for Pekan Olahraga Nasional XVIII Riau - Lafanda, Pynkan; Purba, Ambrosius; Pandji, Tri Damiati (Althea Medical Journal, 2015)
Background: Taekwondo is a martial sport that is often included in competitions, especially in a nationalÂ event such as Pekan Olahraga Nasional (PON) XVIII Riau in September 2012. A taekwondo athlete must havemaximum physical condition in order to achieve maximum performance. West Java taekwondo athletes whoÂ will participate in this national sport event receive centralized exercises as a special preparation stage. ThisÂ study aimed to determine the physical condition profile of male and female taekwondo athletes for PONÂ XVIII RiauMethods: A quantitative descriptive study was conducted in September 2012 to 15 West Java taekwondoÂ athletes for PON Riau XVIII consisting of 7 male athletes and 8 female athletes. Physical conditions measuredÂ were strength, endurance, power, speed, flexibility, cardiorespiratory fitness, agility, and reaction time. TheÂ measurement results were then compared to the physical standards data from the head of National SportsÂ Committee of Indonesia (Komite Olahraga Nasional Indonesia/KONI) and were analyzed by percentagecategoryResults: Characteristics in less category were abdominal muscle endurance (male 71.43% and femaleÂ 100%), cardio respiratory fitness (male 85.71%), and agility (female 37.50%). Characteristics in far categoryÂ were cardio respiratory fitness (female 62.50%) and agility (male 57.14%)Conclusion: The ability of the physical condition of male and female West Java taekwondo athletes for PekanÂ Olahraga Nasional XVIII Riau still needs to be improved to maximize achievement. [AMJ.2015;2(1):281â86]